Outstanding educators for 1985 - Quito, Emerita S. (Animo Repository, 1985)
Philosophy Department Chairperson Emerita Quito was among the 10 teachers selected by Metrobank Foundation as Outstanding Educators for 1985. The teachers were selected from schools all over the country, as announced by Metrobank Foundation President Edgardo B. Espiritu. Awarding ceremonies were held on September 5.